2001
DOI: 10.1002/cne.1333
|View full text |Cite
|
Sign up to set email alerts
|

Expression of growth differentiation factor‐15/ macrophage inhibitory cytokine‐1 (GDF‐15/MIC‐1) in the perinatal, adult, and injured rat brain

Abstract: We and others have recently cloned a new member of the transforming growth factor-beta superfamily, growth differentiation factor-15/ macrophage inhibitory cytokine-1 (GDF-15/MIC-1). Using in situ hybridization and immunohistochemistry, we determined the distribution of GDF-15/MIC-1 mRNA and protein in the perinatal and cryolesioned adult rat brain. The choroid plexus epithelium of all ventricles represents the site of strongest and almost exclusive mRNA expression in the normal perinatal and adult brain. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(137 citation statements)
references
References 32 publications
4
125
2
1
Order By: Relevance
“…With regard to GDF-15, a pro-apoptotic role in several cell lines has been suggested (48 -51). Moreover, our observation that GDF-15 is robustly induced in lesioned cortical neurons (16) can be interpreted in terms of both an anti-or pro-apoptotic role. To clarify this, we started to analyze the effect of GDF-15 and underlying mechanisms on neuronal apoptosis using the well established CGN model (18).…”
Section: Fig 5 Mek1/2 Inhibitor U0126 Decreases Cell Death and Erk mentioning
confidence: 66%
See 1 more Smart Citation
“…With regard to GDF-15, a pro-apoptotic role in several cell lines has been suggested (48 -51). Moreover, our observation that GDF-15 is robustly induced in lesioned cortical neurons (16) can be interpreted in terms of both an anti-or pro-apoptotic role. To clarify this, we started to analyze the effect of GDF-15 and underlying mechanisms on neuronal apoptosis using the well established CGN model (18).…”
Section: Fig 5 Mek1/2 Inhibitor U0126 Decreases Cell Death and Erk mentioning
confidence: 66%
“…At this point, it is not clear whether other types of central nervous system neurons are affected by GDF-15. In a previous study, we had also shown that GDF-15 protein is up-regulated in cortical neurons subsequent to a cold lesion (16). This may indicate functions of the protein in neurons affected by injury and suggest a role of GDF-15 in the execution of either survival or cell death programs.…”
mentioning
confidence: 59%
“…Moreover, NAG-1 is induced by several nonsteroidal anti-inflammatory drugs and other drugs known to have anti-tumorigenic and pro-apoptotic activities (11, 12). In the brain, NAG-1 is expressed in epithelial cells of the choroid plexus and secreted into the cerebral spinal fluid and is reported to function as both a neurotrophic and a neuroprotective factor for midbrain dopaminergic neurons in vivo and in vitro (13,14). Recently, we generated NAG-1 transgenic mice (Cre/NAG-1 Tg/Lox ), which express human NAG-1 in all tissues (15).…”
Section: )mentioning
confidence: 99%
“…Within the central nervous system (CNS), MIC-1/GDF15 is expressed by the choroid plexus and secreted into the cerebrospinal fluid. It is up-regulated as part of the antiinflammatory cytokine network within the CNS in response to injury (Schober et al, 2001), and in this role, it is directly neurotrophic and possibly neuroprotective (Strelau et al, 2000). Cerebrospinal fluid (CSF) concentrations of MIC-1/GDF15 are relatively elevated in human neuronal injury (B. J.…”
Section: Introductionmentioning
confidence: 99%